Mobile phones and farmers’ marketing decisions in Ethiopia - Tadesse, Getaw; Bahiigwa, Godfrey (Elsevier, 2015)
This paper examines the impact of mobile phones on farmers’ marketing decisions and prices they receive based on household- and village-level information collected from rural Ethiopia. It explains the reason for the weak impact of mobile phones observed in this study as well as in previous studies in Africa. We argue that even though many farmers participate in information searching, the number of farmers who use mobile phones for information searching is very small. The reason for such low use of mobile phones for information searching seems to be lack of relevant information that can be accessed through mobile phones.